Single-trial classification of an EEG-based brain computer interface using the wavelet packet decomposition and cepstral analysis - Lodder, Shaun (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.